Plasma Tau Levels in Cognitively Normal Middle-Aged and Older Adults - Chiu, Ming-Jang; Fan, Ling-Yun; Chen, Ta-Fu; Chen, Ya-Fang; Chieh, Jen-Jei; Horng, Herng-Er (Frontiers in Aging Neuroscience, 2017)
Using an ultra-sensitive technique, an immunomagnetic reduction assay, the plasma tau level can be measured to a limit of quantification of pg/ml. In total 126 cognitively normal middle-aged and older adults (45 to 95 years old) were recruited. The plasma tau levels were significantly higher in the older group (aged 65 to 95) 18.14 ± 7.33 pg/ml than those in the middle-aged group (aged 45 to 64) 14.35 ± 6.49 pg/ml when controlled gender and ApoEε4 carrier status (F = 3.102, P = 0.029). The ApoEε4 carriers had higher plasma tau levels than the non-carriers when controlled age and gender (F = 6.149, P = 0.001). Men had higher plasma tau levels than their women counterparts when controlled ApoEε4 carrier status and gender (F = 6.149, P = 0.001). The plasma tau levels were found to be positively associated with their ages (r = 0.359, P < 0.001). Regression analysis showed that age explained approximately 13% of the variance in the plasma tau levels, and explained more than 10% of the variance in the volumes of the hippocampus and white matter hypodensity (R2 change 0.123~0.167, all P < 0.001), and explained less than 10% of the variance in the volume of the amygdala, and central part of the corpus callosum (R2 change 0.085~0.097, all P = 0.001). However, the plasma tau levels do not further explain any residual variance in the volume of brain structures. In conclusion, the effect of age on the plasma tau levels should always be considered in clinical applications of this surrogate biomarker to middle-aged and elderly subjects.